Successful esophageal endoscopic submucosal dissection with a transoral endoscope after stepwise scope bougienage of post‐endoscopic submucosal dissection stricture. Issue 1 (22nd October 2020) - Takita, Maiko; Ohata, Ken; Negishi, Ryoju; Minato, Yohei; Muramoto, Takashi
Abstract : Endoscopic submucosal dissection (ESD) for extensive esophageal cancer inevitably causes a post‐ESD stricture. It may be difficult to perform additional ESD if a new lesion develops on the anus side of the post‐ESD stricture. We sometimes perform balloon dilation of post‐ESD stricture in advance, so we could perform ESD using a transoral scope; however, there is a risk of balloon dilation causing severe tearing of the lesions if it is located near the stricture. A 68‐year‐old man who had undergone ESD for esophageal cancer several times was diagnosed with early esophageal cancer. The lesion was located near the anus side of the post‐ESD stricture. Unfortunately, the lesion was located on another post‐ESD scar. Although ESD using a transnasal scope was a useful option, it was expected to be challenging as the submucosal layer was thought to have severe fibrosis. We attempted to perform ESD with a transoral endoscope after stepwise scope bougienage of post‐ESD stricture. Abstract : Endoscopic submucosal dissection (ESD) for extensive esophageal cancer inevitably causes a post‐ESD stricture. It may be difficult to perform additional ESD if a new lesion develops on the anus side of the post‐ESD stricture. We attempted to perform ESD with a transoral endoscope after stepwise scope bougienage of the post‐ESD stricture.